Importance of the Concept of Constitutional Identity for Ensuring European Union Law in Lithuania - Jarašiūnas, Egidijus (Teisė, 2022)
This paper examines issues related to the significance of the concept of constitutional identity, which has emerged in the jurisprudence of the Lithuanian Constitutional Court, and its impact on ensuring European Union law in Lithuania. This concept, which also unites the principle of geopolitical orientation, of which membership in the European Union is an integral part, should contribute to guarantee a balance between the legal systems, which is also significant for ensuring EU law in Lithuania.